Clinical characteristics of lean and non-lean non-alcoholic fatty liver disease: a cross-sectional study - Mengyan Xu; Rui Gong; Jiao Xie; Sanping Xu; Shi Wang (Nutrition & Metabolism)
Abstract Introduction Non-alcoholic fatty liver disease (NAFLD) affects more than a quarter of the global population and has become the world’s number one chronic liver disease, seriously jeopardizing public life and health. Despite the new terminology of metabolic dysfunction-associated steatotic liver disease (MASLD) has been proposed, the mechanisms underlying the heterogeneity across BMI stratification in non-alcoholic fatty liver disease (NAFLD) remain unclear. The aim of this study was to reveal the differences in metabolic and fibrotic characteristics between lean (BMI < 23 kg/m2) and non-lean NAFLD in an Asian population. Methods The current study collected NAFLD patients from the physical examination population. Patients were divided into two groups by BMI to compare their clinical parameters, including lean (BMI < 23 kg/m2) and non-lean (BMI ≥ 23 kg/m2) and fibrosis subgroups (with a threshold of LSM = 8 kPa) and analyzed for risk factors by logistic regression models. Results Of the 11,577 NAFLD patients who participated in the study, there were 916 lean and 10,661 non-lean. The non-lean group was younger than the lean group (median age 50 vs. 52 years, P < 0.001) and had a significantly higher prevalence of hypertension (28.0% vs. 18.3%), diabetes mellitus (10.1% vs. 6.1%), and liver fibrosis (9.1% vs. 5.1%) (all P < 0.001). Analysis of metabolic indexes showed that TyG, TyG-BMI, TG/HDL-C and APRI were higher in the non-lean group (all P < 0.001). Gender stratification revealed that ALT was significantly higher in the male non-lean group, while HDL-C was lower in the female non-lean group (1.35 vs. 1.47 mmol/L). Multiple regression suggested that the risk of fibrosis was independently associated with CAP values and fasting glucose, BMI, direct bilirubin, globulin, and age in the non-lean group, whereas the risk was mainly driven by GGT and ALP in the lean group. Conclusions Non-lean NAFLD patients showed more significant metabolic disturbances and risk of liver fibrosis. Although metabolic indicators (TyG, FIB-4) have limited predictive value for liver fibrosis, they are strongly associated with metabolic risk in MASLD.